3x+6(12x)=6(1x)-5

Simple and best practice solution for 3x+6(12x)=6(1x)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6(12x)=6(1x)-5 equation:


Simplifying
3x + 6(12x) = 6(1x) + -5

Remove parenthesis around (12x)
3x + 6 * 12x = 6(1x) + -5

Multiply 6 * 12
3x + 72x = 6(1x) + -5

Combine like terms: 3x + 72x = 75x
75x = 6(1x) + -5

Remove parenthesis around (1x)
75x = 6 * 1x + -5

Multiply 6 * 1
75x = 6x + -5

Reorder the terms:
75x = -5 + 6x

Solving
75x = -5 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
75x + -6x = -5 + 6x + -6x

Combine like terms: 75x + -6x = 69x
69x = -5 + 6x + -6x

Combine like terms: 6x + -6x = 0
69x = -5 + 0
69x = -5

Divide each side by '69'.
x = -0.07246376812

Simplifying
x = -0.07246376812

See similar equations:

| 1-8+1-10=1-x | | 4x^2-24v+36=0 | | 3(x-0.8)=15x+16/7x | | (7c-5)(7c+5)=0 | | 49+(x+3)=90 | | 3b-4.4=2.6-6b | | 3b-4.4=2.6-6b | | 1x-5=1 | | a^2+4a+12=0 | | b-3b=2 | | 5(2+x)=4(x-2) | | 12x/18=36 | | 7y-2(6y+29)=-28 | | ln(5x-3)=0 | | -x/5-1.2=6.6 | | 2u^2+u+6=0 | | (2x+5)/(x-8)+(x+13)/(8-x) | | 9.95+.30s= | | 7-1/4=9 | | 8x-(x-21)=7(x+3) | | 1/3-3=-3 | | 3/2-5 | | 4y-7(3y+12)=-67 | | 12m=3m+10 | | y=2+14x | | 2/3(x-9)1/3x=7x-15 | | X(x-3)+4x-3=8x+x(3x+x) | | 3/n=9/3 | | x+26=2x+40 | | 3/2-1 | | 2y+8y=16 | | -2=4n |

Equations solver categories